2022
DOI: 10.3390/en15145068
|View full text |Cite
|
Sign up to set email alerts
|

Green Finance and Green Energy Nexus in ASEAN Countries: A Bootstrap Panel Causality Test

Abstract: Green energy is a crucial component in addressing expanding energy demands and combating climate change, but the possible negative repercussions of these technologies are frequently disregarded. Green energy’s deployment is tied to environmentally sustainable development goals (SDGs). It can only be achieved by scaling up the finance of investment that provides environmental benefits through new financial instruments and new policies, such as green banks, green bonds, community-based green funds, green central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…The Malmquist index approach has certain benefits, such as the fact that it does not require any price information to estimate TFP; nevertheless, it also has some drawbacks. In particular, it is sensitive to the group of nations being contrasted as well as the number of variables being accounted for in the model [42]. Estimates of TFP are likely to be plagued by measurement inaccuracies if they are not based on a representative sample of many nations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Malmquist index approach has certain benefits, such as the fact that it does not require any price information to estimate TFP; nevertheless, it also has some drawbacks. In particular, it is sensitive to the group of nations being contrasted as well as the number of variables being accounted for in the model [42]. Estimates of TFP are likely to be plagued by measurement inaccuracies if they are not based on a representative sample of many nations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…suggested that green credit imposes credit limitations on highly polluting enterprises, hence increasing the requirements for corporate funding. Consequently, corporations are compelled to take measures to avoid environmental pollution right from its origin [ 50 ]. also contend that green credit has diminished the financial capability of significantly polluting enterprises [ 51 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, there is another view that debate that financial institutions are less likely to finance firms dealing with green technologies provided the government sector has good information regarding the hazard linked with innovative projects (Ahmed et al, 2022; Beniwal & Kumar, 2020; Ionescu, 2023; Olmos et al, 2012). This is because banks tend to reduce their financial risks by investing in close‐to‐market technologies, which are able to produce market revenues already in the short‐to‐medium term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the expansion of renewable energy technologies (RETs) makes it possible to strengthen energy security by diversifying the energy mix, while contributing to a reduction in fossil fuel dependence and greenhouse gas (GHG) emissions (Roslan, 2021). Many countries have taken the step to promote renewables with environmental policy frameworks (Ahmed et al, 2022); however, they still report a low fraction of world electricity production. 1 This reality proposes that there are still some deficient connections between the possible benefits of renewables and their execution, and these missing links need investigating.…”
Section: Introductionmentioning
confidence: 99%